2019
DOI: 10.1177/2309499019834674
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tibial slope on anterior cruciate ligament graft failure risk is dependent on graft positioning

Abstract: Background: Increased lateral tibial posterior slope (LTPS) is associated with higher anterior cruciate ligament (ACL) reconstruction (ACLR) failure rate. Transportal central femoral footprint ACLR is associated with higher failure rate compared to transtibial high anteromedial footprint ACLR due to graft anisometry. The purpose of this study was to investigate whether the influence of tibial slope on ACL graft failure risk is dependent on graft positioning. Material: Of the 1480 consecutive hamstring ACLRs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Previous studies reached similar conclusions with respect to intact ACLs compared with torn ACLs. 14 , 39 , 80 , 81 Additional studies have also reported increased PTS with 1 or more patients undergoing revision ACLR compared with those undergoing primary ACLR. 20 , 31 , 72 A previous meta-analysis that included 14 studies reported greater lateral PTS in individuals with ACL injury than in those with intact ACLs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reached similar conclusions with respect to intact ACLs compared with torn ACLs. 14 , 39 , 80 , 81 Additional studies have also reported increased PTS with 1 or more patients undergoing revision ACLR compared with those undergoing primary ACLR. 20 , 31 , 72 A previous meta-analysis that included 14 studies reported greater lateral PTS in individuals with ACL injury than in those with intact ACLs.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of the patients, the transtibial ACLR technique was used. In our own previously published study on this topic, 2 we found that an increased tibial slope had a solely significant impact on the failure risk after transportal ACLR, not after transtibial ACLR. Given the admirable number of patients in the present report, an isolated evaluation of the effect of an increased tibial slope on the revision risk after transportal ACLR would be of great interest.…”
mentioning
confidence: 53%
“…In this study, the abnormal value of PTS was considered ≥12° based on the results of previous literature. 7,25,28,30,38…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the abnormal value of PTS was considered 12°based on the results of previous literature. 7,25,28,30,38 MRI Evaluations. MRI was performed using a 1.5-T superconducting magnet (Signa; GE Medical Systems) using a standardized institutional protocol.…”
Section: Data Collectionmentioning
confidence: 99%